Psychoanalysis of The Main Character in The Joker Movie - Rizki Anandi; Vera Magria; Dedi Efendi (Universitas Muara Bungo, 2022)
This research title is Psychoanalysis of The Main Character of The Joker Movie, analysed about psychoanalysis and kind of character of the main character in the Joker movie by Todd Phillips, this movie tells the story of a person with a psychological disorder who lives with his mother, he is a good boy and always takes care of his mother, works for his mother until finally he turns into a murderer because he is often bullied by people around him. The method which is used in this research is descriptive qualitative method proposed by Bogdan and Biklen (1982) who state that the collected data which is used this method is in form of words as picture rather than numbers related to Joker Movie. The data is analysed through some ways: Identifying, Classifying, Analising, and Conclusion. The result of this research are stated as follows: firstly, the personality of the main character that found in this movie there are id, ego, and superego. Secondly, from 20 data that found in the movie, the id is the most personality appearing in this movie., there is 7 data of id, 5 data of ego, and 2 data of super ego. Then writer also found 6 data kind of character of the main character there are flat character that appear in the beginning of the movie, round character that appear in the middle of the movie, protagonist that appear in the beginning of the movie, antagonist that change in the middle of the movie, and dynamic character, from the kind of characters above the round character is the dominant appear from the others, because the characterization of Arthur is always changing.